SISTEM PAKAR DIAGNOSIS PENYAKIT KANKER PAYUDARA DAN CARA PENANGANANNYA - Dewi Ayu Puspitawati (Jurnal Techno Nusa Mandiri, 2018)
At the moment, maybe everyone thinks the cancer is malignant and cannot be cured. The statement is wrong because cancer can be prevented and cured as long as the treatment is not too late. It is very important for everyone to know the initial symptoms and cancer risk factors in order to make efforts to prevent the trigger of the emergence of the disease and immediately take appropriate action to eradicate it because late handling can be fatal. Doctors and researchers have written many books so far, how to deal with breast cancer. However, the advice of doctors is often not supported by the progress made by the researchers. And researchers often fail to translate their knowledge into practicalsuggestions that can be used by the community. In this expert system the inference technique used is tracking and searching. The tracking technique used is forward tracking (Forward Chaining), while the search for decisions from each problem is used the Best First Search search method, a search that combines two existing search methods, namely the Breadth First Search method and the Depth First Search method. Therefore, the author makes a webbased application program to help the general public who want to know about breast cancer information and how to handle it.